Considerations in designing is services quality (ISSQ) assessment - Poobalan, Masilamani; Alias, Rose Alinda; Abdul Rahman, Azizah (2002)
This paper is divided into two major parts. The first part begins by introducing information system service quality (ISSQ) model. The model identifies components and elements that encompass ISSQ in an organization. The model is currently being developed by one of the authors based on fieldwork conducted in institutes of higher learning (IHLs) in Malaysia and surrounding region. Part two describes the use of ISSQ model as a basis for ISSQ assessment. This is done by identifying elements involved in the intricacies of establishing, deploying, and receiving information system services (ISS). Even though the ISSQ model is based on IHLs, the elements are generalized in order to fit all types of organizations. Part two ends with description of relationships among various elements involved in assessment of ISSQ.